2009
DOI: 10.1016/j.pbb.2009.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Differential involvement of the norepinephrine, serotonin and dopamine reuptake transporter proteins in cocaine-induced taste aversion

Abstract: Despite the impact of cocaine's aversive effects on its abuse potential, the neurochemical basis of these aversive effects remains poorly understood. By blocking the reuptake of the monoamine neurotransmitters dopamine (DA), norepinephrine (NE) and serotonin (5-HT) into the presynaptic terminal, cocaine acts as a potent indirect agonist of each of these systems. The following studies attempted to assess the extent of monoaminergic mediation of cocaine's aversive effects using conditioned taste aversion (CTA) l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 53 publications
1
14
0
Order By: Relevance
“…In fact, multiple genes in the NAc are differentially expressed in drug naïve and MA-exposed MADR line mice, which could contribute to differential neuroadaptation. Drug naïve high and low line mice, for example, show differential expression of the gene that codes for the noradrenergic transporter, which is thought to contribute to the negative effects of psychostimulants (Jones et al, 2009; Schank et al, 2008). However, how this gene, or others that are differentially expressed in the MADR lines, contributes to sensitivity to anxiogenic and aversive effects of MA remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, multiple genes in the NAc are differentially expressed in drug naïve and MA-exposed MADR line mice, which could contribute to differential neuroadaptation. Drug naïve high and low line mice, for example, show differential expression of the gene that codes for the noradrenergic transporter, which is thought to contribute to the negative effects of psychostimulants (Jones et al, 2009; Schank et al, 2008). However, how this gene, or others that are differentially expressed in the MADR lines, contributes to sensitivity to anxiogenic and aversive effects of MA remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Antagonizing NE activity removes this inhibition allowing cocaine to induce stronger aversions. In support of this, Serafine and Riley (2009) have recently shown that preexposure to cocaine potentiated aversions induced by the NE transporter (NET) inhibitor desipramine (Serafine and Riley, 2009), suggesting that tolerance to cocaine during preexposure (likely through its actions on NET) resulted in the weakening of any inhibitory effects NE may have on desipramine’s aversive effects (for similar investigations and findings with mice; see Jones et al, 2009). Although collectively this work suggests that NE activity may limit the aversive effects of cocaine (and desipramine), preexposure to desipramine attenuated cocaine-induced CTAs (Serafine and Riley, 2009).…”
Section: Discussionmentioning
confidence: 86%
“…To date, no direct pharmacological studies have been conducted to assess the effects of 5-HT receptor activation (or antagonism) on the aversive effects of cocaine. Our laboratory has recently used the cross-drug preexposure preparation to assess the effects of exposure to the selective serotonin reuptake inhibitor (SSRI) fluoxetine on aversions induced by cocaine (and vice versa; Serafine and Riley, 2010; see also Jones et al, 2009 for a similar assessment with mice). Under these conditions, fluoxetine preexposure did not attenuate cocaine-induced CTAs, suggesting that the two do not share a common aversive effect, although higher doses of fluoxetine may attenuate cocaine-induced aversions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations